Values, personality traits, and packaging‐free shopping: A mixed‐method approach. Issue 2 (11th February 2022) - Gordon‐Wilson, Sianne; Modi, Pratik; Eastman, Jacqueline K.
Abstract: This research examines packaging‐free shopping, which contributes to reducing the negative impact of plastic packaging on the environment, and its' relationship with green consumption values, value consciousness, and psychological traits. A mixed‐methods approach is adopted with quantitative followed by qualitative research. Study 1 recruits 240 respondents from social media and the lead author's university website to examine different factors that increase consumers' likelihood of packaging‐free shopping. Study 2 recruits packaging‐free shoppers from Facebook Pages, explores these findings and provides further insights. Study 1 finds that consumers are driven more by green consumer values than by value consciousness, and consumers who are more conscientious are more likely to do packaging‐free shopping. Study 2 supports this by finding that green consumer values drive packaging‐free shopping, but this in only one part of their green efforts. The research contributes by illustrating the importance of conscientiousness specifically in the domain of packaging‐free shopping and that these packaging‐free shoppers are not driven in terms of value for money but by addressing their green consumer values. We recommend that packaging‐free retailers and policy makers utilize promotional efforts to communicate how packaging‐free shopping provides a balance with consumers' green values for these shoppers, how it fits in with their other green efforts, and how these shopping efforts are making a difference in helping the environment.